Caries of First Primary Molars Requiring Glass Ionomer Cement Versus Composites as Restorative Materials - Niharika Kotian, EMG Subramanian, Ganesh Jeevanandan, Mebin George Mathew (Institute of Medico-legal Publications Pvt Ltd, 2020)
In the present study comparison of the clinical preference of glass ionomer versus resin composite in primarymolars by dentists was performed. This was done to evaluate which material will provide better clinicalperformance for pediatric patients based on esthetic , functional and biological properties.Data collectedfrom a patient management software. A total of 1609 children were included in the study who requiredclass 1 restorations . The data was tabulated on an excel sheet and transferred to SPSS software wherestatistical analysis was further performed. 232 children were indicated for composite restoration and 1377children were indicated for glass ionomer cement for class 1 restorations. There was no statistical significantdifference between both the restorative material groups (p>0.05).We observed that dentists preferred glassionomer cement over composite to restore class 1 cavity in primary molars.